Kesalahan Penggunaan Verba Dinatory BahasaJepang pada Mahasiswa Pemelajar Bahasa Jepang - Dance Wamafma (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Udayana, 2025)
The standard structure of Giver ga Receiver ni camera wo yaru/kureru' follows the view of Love regarding Japanese Donatory Verbs.. The structure keeps some rules that Japanese learners rarely observe. One of the aspects that is rarely seen is the social status of the subject filler Giver, the recipient of Receiver (dative) and Speaker (speaker). These three components have a great influence on the filler of the predicate, yaru or kureru. If the social status of S is inferior to G, while the social relationship between S and R meets the criteria of uchi in blood or insider relationships, then the embedded verb is kureru. This consideration is the background of this research. Meanwhile, the purpose of this article is to illustrate the form of error in the use of Donatory Verbs sentences. The data collection method was carried out through questionnaires. The questionnaire details are compiled based on cases of incorrect in Indonesian to youngen the analysis of the sentence of acceptance in Japanese. The results of the analysis found that there are quite massive difficulties in the use of verbs that are in harmony with the social relations of G, R, S, as well as the placement of the role of G, R, S and the social status they hold. The analysis of the questionnaire also touched on the interference of the mother tongue structure into Japanese, the difficulty of considering the gradation of the keigo speech act (敬語) according to the view of Love on the rules of Donatory Verbs. A small percentage of respondents used a sentence translation unit with a selection of words or categories that did not match